Evaluation of antisense oligonucleotide loaded chitosan nanoparticles; characterization and antisense effect - ÖZBAŞ, SUNA (GOVI-VERLAG PHARMAZEUTISCHER VERLAG GMBH, 2009)
The objective of this study was to investigate the effect of different formulation parameters [i.e. molecular weight and concentration of chitosan, concentration of tripolyphosphate (TPP) and use of alginate] on physico chemical and antisense properties of antisense oligonucleotide (AsODN) loaded chitosan nanoparticles (NPs). Preparation methods of phosphodiester (PO) and phosphorothioate (PS) AsODNs-NPs were also compared. AsODNI was designed to target the beta-galactosidase (beta-gal) gene. HeLa cells were used for in vitro transfection studies and beta-gal was assayed spectrophotometrically. AsODN-NPs obtained were in general positively charged with size between 221.4-525.7 nm depending on formulation. Encapsulation efficiency of NPs depended on the type of backbone of the AsODN. PO-AsODN encapsulation into NPs (78-94%) was less efficient than PS encapsulation (91-98%). The pH of the chitosan solution affected AsODN entrapment. PO-NPs exhibited faster AsODN release than NPs containing PS. In general higher beta-gal inhibition was obtained after transfection of AsODN-NPs in cell culture studies. PS-NPs exhibited a higher inhibition effect and the highest (90.71%) inhibition was obtained with formulation PT-2. PS-adsorbed NPs showed an 88% reduction in beta-gal. This study can form the basis for forthcoming in vivo studies related to AsODN carrier systems that will use chitosan.
Keywords: POLYALKYLCYANOACRYLATE NANOPARTICLES; GENE DELIVERY; FORMULATION; SYSTEM; INHIBITION; CARRIERS; DNA